An effectiveness of appplication of facilities management at hotel managed university / Ahmad Syafiq Mohamed Kamal - Mohamed Kamal, Ahmad Syafiq (2012)
The hotel management is a profession that had been long existed for managing the operation hotels. Rarely, we heard about the hotel managed by university. In Malaysia, only a few hotel managed by university such UiTM hotel and UNITEN hotel. According to San T.K. (2005), the main purposes of hotel management is to ensure that the customer of hotel can enjoy their stay in the hotel with maximum comfort. So, to fulfil this purposes, the hotel management not only provide best service, but also provide good facilities which will be enjoyed by visitors. Therefore, facilities management are expected can be applied in hotel management. So, to prove the applicable of facilities management at hotel managed by university, the management perspective and understanding about this management had been important factor for determining it. This study is to identify the perspective from hotel management about facilities management at hotel managed by university. Beside, every hotel has provides various type of facilities. Not at all facilities provided by hotel get good satisfaction by visitor. Therefore, another objective is to determine the satisfaction level by visitors about the facilities provided at hotel managed by university. All objective for this study will be finding in an Effectiveness of Application Facilities Management at Hotel Managed By University. This dissertation has six chapters, it including concept of facilities management, the important of facilities management and organisation structure of facilities management. To fulfil the requirement of objective of this study, case study area are selected at UiTM Shah Alam hotel, Intekma Resort and Convention Centre (IRCC) and UiTM Dungun hotel.